ANALISIS PERFORMA SISTEM KONTROL VALVE TURBIN PLTU DI BANTEN - Arvin Satria (2022)
PLTU is an abbreviation of steam power plant, PLTU uses coal as fuel to be able to drive a turbine and generate a magnetic field in a generator to make electrical energy that can be used by consumers. In power generation equipment, namely in the turbine area, researchers found a problem in the form of an error in reading data on the turbine valve which caused a decrease in performance at the turbine and generator valve, with a decrease in performance at the turbine and generator valve, an analysis was needed to justify a decrease in performance. This results in a decrease in the electrical energy that can be produced by the PLTU. The analysis carried out is to collect the required parameter data and compare it with several conditions as well as a simulation so that facts related to the problem can be obtained and find solutions. Keyword: PLTU, Turbine, Turbine Valve, Performance